The wurst is yet to come : a bed-and-breakfast mystery - Daheim, Mary. (New York : William Morrow, 2012)
When she volunteers at the State B&B booth during Oktoberfest, trying to win some allies to save her inn, Judith McMonigle Flynn stumbles on a dead body and, agreeing to not get involved, convinces her cousin Renie to pose as the sleuth while she does the dirty work to solve this crime.
Keywords: Flynn, Judith McMonigle (Fictitious character) -- Fiction; Women detectives -- Fiction; Bed and breakfast accommodations -- Fiction; Detective and mystery stories; Mystery fiction